Amylose content and pre-freezing regulate the structure and oil absorption of polyelectrolytes-based starch cryogel. (15th February 2023) - Jiang, Yi; Junejo, Shahid Ahmed; Jia, Xiangze; Zhang, Bin; Fu, Xiong; Huang, Qiang
Abstract: Starch cryogel is a potential material for oil absorption. This study provided a facile and convenient polyelectrolyte-based preparation strategy of starch cryogel, in which the structural properties of the cryogel were regulated by amylose content and pre-freezing without long-time retrogradation. Sodium laurate was used as a guest model to form starch-fatty acid salt complex (polyelectrolyte). The amount of amylose content and sodium laurate added led more polyelectrolytes, significantly increased V-type crystallinity from 3.72 % to 22.40 % and complexing index from 4.32 % to 28.48 %. As the uniform pore structure improved the oil absorption ability of starch cryogel, the starch cryogel prepared by waxy maize starch followed by quick pre-freezing showed the highest specific surface area (9.87 m 2 /g) and oil absorption capacity (32.94 g/g). Our findings suggest that polyelectrolyte properties have great potential in the preparation of starch-based cryogels, which could be applied in the design of novel starch-based porous materials.